When the mask comes off: Mothers' experiences of parenting a daughter with autism spectrum condition. (August 2020) - Anderson, James; Marley, Charles; Gillespie-Smith, Karri; Carter, Leonie; MacMahon, Ken
There is limited knowledge and research on the experiences of having a daughter with autism spectrum condition from a mother's perspective. This study aims to explore the experiences of mothers who care for a daughter with autism spectrum condition, with a particular focus on female autism spectrum condition presentation. Ten mothers of daughters with autism spectrum condition took part in a semi-structured interview. Interpretative phenomenological analysis was used to analyse the data. Five superordinate themes emerged: 'Girls have autism too', 'She's a chameleon', 'The impact of the diagnosis', 'Impact on mums' and 'Day-to-day life'. These findings add to our knowledge of how female autism spectrum condition presents and of the experiences directly related to being the mother of a daughter with autism spectrum condition. The findings have implications for clinicians that carry out autism spectrum condition assessments and provide insights into areas where additional support can be provided to mothers and daughters. Lay abstract: Parents of children with autism spectrum condition report increased stress and difficulties compared with parents of typically developing children. Our knowledge and understanding of how autism spectrum condition presents in autistic females is currently limited and parents of this population may experience challenges when raising their daughter. Given that mothers are often the main caregiver of a child with autism spectrum condition, they may have useful insights into the experiences of parenting a daughter with autism spectrum condition. Therefore, a qualitative study was undertaken to explore what mothers' experiences are of parenting a daughter with autism spectrum condition. Semi-structured interviews were conducted with 10 mothers of daughters with autism spectrum condition. The interviews were analysed using interpretative phenomenological analysis. Five main themes emerged from the qualitative study ('Girls have autism too', 'She's a chameleon', 'The impact of the diagnosis', 'Impact on mums' and 'Day-to-day life'). The findings of this study expand our current knowledge of the experiences and challenges faced by mothers raising a daughter with autism spectrum condition. Mothers hold a vast amount of knowledge on their daughters' autism spectrum condition which could inform the diagnostic process and clinical practice. Considering these results, it is important that clinicians support mothers and the family system around children with an autism spectrum condition diagnosis.